(untitled) (Applied Biological Research, 2011)
Heterosis phenomena was studied for 30 inter-varietal (indica x indica, japonica x japonica) crosses and 15 inter-subspecific crosses generated through different mating designs in Kharif 2008 and evaluated for heterosis phenomena for various morpho-agronomic and other traits under different agro-ecologies of Kashmir. The basic experimental material comprized of 12 genotypes with six types belonging to each sub-specific group. For grain yield plant-1 only six inter varietal crosses Jhelum x SK-382, Jhelum x China 1039, SK-382 x SR-1, SR-1 x Chenab, GS-504 x K-508 and Kohsar x K-508 and no inter-subspecific cross proved significantly superior over commercial check. For days to 50% flowering, an important economic character, only cross combinations Koshihikari x GS 508, Koshihikari x K-508 and Kohsar x K-508 flowered earlier as compared to better parent. The standard heterosis for early flowering was observed on GS 504 x K-508 and Kohsar x K-508. Negative heterosis was observed for grain yield plant-1 in inter-subspecific crosses, whileas heterosis for all economic characters was recorded in some inter-varietal crosses. Negative heterosis was pronounced for most of the cross combinations with respect to most important economic traits in case of inter-subspecific pool because of high magnitude of hybrid sterility. There was one to one correspondence between per se performance and heterotic estimates, but such was not the case with SCA effects. The crosses with high SCA effects viz-a-viz with high standard heterosis can be exploited to develop early desirable segregants for grain yield and other morpho-agronomic traits.